Comparative solution studies and cytotoxicity of gallium(III) and iron(III) complexes of 3-hydroxy-2(1H)-pyridinones. (1st November 2019) - Enyedy, Éva A.; Mészáros, János P.; Spengler, Gabriella; Hanif, Muhammad; Hartinger, Christian G.
Graphical abstract: The solution speciation of Ga(III) and Fe(III) complexes of two (O, O) donor bearing alkoxycarbonylmethyl-3-hydroxy-2(1 H )-pyridinone ligands was characterized. Moderate stabilities were observed with [ML3 ] complexes predominating at physiological pH. Significant decomposition of the Ga(III) complexes occurs at low concentration leading to negligible cytotoxic activity in human adenocarcinoma cells. Abstract: The stoichiometry and stability constants of the gallium(III) and iron(III) complexes of two alkoxycarbonylmethyl-3-hydroxy-2(1 H )-pyridinone ligands were determined by means of pH-potentiometry, UV–Vis spectrophotometry and 1 H and 71 Ga NMR spectroscopy in aqueous solution. The cytotoxicity of one of the gallium(III) complexes was also measured in multidrug resistant/non-resistant human colon adenocarcinoma cell lines. Iron(III) forms complexes with the studied 3-hydroxy-2-pyridinones of higher stability than gallium(III), while the obtained pFe values are significantly lower (pFe: 14.95, 15.06; pH 7.4, c M  = 1 µM, c L  = 10 µM) compared to those of typical iron binders such as deferiprone or transferrin. The moderate gallium(III) and iron(III) binding ability of the compounds stands for lower solution complex stability compared to that of analogous bidentate non-substituted 3-hydroxy-2-pyridinone or 3-hydroxy-4-pyridinone (O, O) donor ligands. Tris-ligand complexes of the general formula [ML3 ] (M = Ga, Fe) predominate at physiological pH for both ligands. No interaction with cell culture medium components was observed in the millimolar concentration range of gallium(III) complexes, however they can suffer significant decomposition at biologically relevant low concentrations leading to negligible cytotoxic activity. The redox potential of the studied iron–3-hydroxy-2-pyridinone complex (E1/2  = −597 mV at pH 7.4) falls into the range that is typical of iron(III) complexes with conventional bidentate (O, O) donor-containing chelators.